2004
DOI: 10.1002/ajmg.a.30410
|View full text |Cite
|
Sign up to set email alerts
|

Rett syndrome in females with CTS hot spot deletions: A disorder profile

Abstract: From a series of 107 females with Rett syndrome (RTT), we describe the long-term history of ten females with a deletion in the C-terminus of the MECP2 gene. We observed that their disorder profile is clinically recognizable with time and different from other atypical and milder RTT phenotypes. In females with hot spot deletions in the C-terminus, dystonia is present from childhood and results in a serious spine deformation in spite of preventive measures. Their adaptive behavior is surprisingly better preserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
56
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 19 publications
7
56
1
1
Order By: Relevance
“…However, these apparently milder mutations also appear to be more likely to have other behavioural problems [32]. C terminal mutations are usually mild in severity [33]; they also had a low prevalence of sleep problems. We found that cases with a large MECP2 deletion were the most likely to have a sleep problem and night-time laughter was reported in all cases.…”
Section: Discussionmentioning
confidence: 98%
“…However, these apparently milder mutations also appear to be more likely to have other behavioural problems [32]. C terminal mutations are usually mild in severity [33]; they also had a low prevalence of sleep problems. We found that cases with a large MECP2 deletion were the most likely to have a sleep problem and night-time laughter was reported in all cases.…”
Section: Discussionmentioning
confidence: 98%
“…The identified mutation was an 86 bp deletion in the deletion-prone region at the C-terminus of the fourth exon (1140del86). The boundaries of this deletion hot-spot region are located between nucleotides 1050 and 1200, giving rise to intragenic deletions of various sizes and accounting for approximately 10% of RTT mutations in females (13). Although the late truncation of the MeCP2 protein results in intact methyl-binding and transcriptional repression capacity, it nevertheless prevents the highest level of chromatin compaction (19).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of causative alterations (including missense, nonsense, and frameshift mu-tations) occur in exons 3 and 4, which encode the MeCP2 functional domains, the MBD and the TRD domain, respectively (12). The C-terminal region located downstream of the TRD is prone to deletions of various sizes resulting in the production of truncated proteins (13). Large rearrangements encompassing even whole exons and more specifically duplications ranging from 400 to 800 kilobases (Kb) have also been detected in RTT patients, accounting for ϳ10% of RTT cases.…”
mentioning
confidence: 99%
“…Roughly 57.1% (8/14) of the patients with atypical RTT possessed mutations in their MECP2 sequences. Recent reports described a range of 65-79% for the mutation detection rate among patients with atypical RTT (Smeets et al , 2005. Kanmmoun et al recommended selecting well-defined clinical criteria while searching for MECP2 mutations, as all individual variables did not exhibit similar weights (Kammoun et al 2004).…”
Section: Cdkl5 Mutation Detection By Dhplc Analysismentioning
confidence: 99%